Dark chocolate - al-magbary, omar Hussein omar (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Effect of main substances in cacao of dark chocolate li ( Anandamide – Tryptophan – Caffeine – Theobromine ) but the main substance in cacao of dark chocolate and to give the main effect of it, the Flavonoid and its six types and the main two effect of flavonoid ( antioxidant activity– antiinflammatory activity ), meeting of these effect to help some cardiodiseases such as Atherosclerosis, Finally its effect on apatite.
The dark chocolate generally contain mainly cacao and milk and less amount of sugar. The cacao made from beans from the Theobroma cacao tree was first discovered in the Mesoamerica population uses of cacao or chocolate either as a primary remedy or as a vehicle to deliver other medicines